Asymmetric Catalytic Assembly of Triple‐Columned and Multilayered Chiral Folding Polymers Showing Aggregation‐Induced Emission (AIE). Issue 7 (19th January 2022) - Wang, Jia‐Yin; Tang, Yao; Wu, Guan‐Zhao; Zhang, Sai; Rouh, Hossein; Jin, Shengzhou; Xu, Ting; Wang, Yu; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; Li, Yunze; et al.
Abstract: Unprecedented chiral multilayer folding 3D polymers have been assembled and regulated by uniform and differentiated aromatic chromophore units between naphthyl piers. Screening catalysts, catalytic systems and monomers were proven to be crucial for asymmetric catalytic Suzuki–Miyaura polycouplings for this assembly. X‐ray crystallography of the corresponding dimers and trimers revealed the absolute configuration and the intermolecular packing pattern. Up to 61 960 M w /41 900 M n and m / z 4317 for polymers and oligomers, as confirmed by gel permeation chromatography (GPC) and MALDI‐TOF MS, indicated that these frameworks were composed of multiple stacked layers. The resulting multiple π‐assemblies exhibited remarkable optical properties in aggregated states (photoluminescence in solids and aggregation‐induced emission in solutions), as well as reversible redox properties in electrochemical performance. Abstract : A first asymmetric catalytic approach to multilayer 3D folding polymers by using Suzuki–Miyaura cross‐coupling in the presence of chiral catalysts. The resulting multiple π‐assemblies exhibited remarkable optical properties in aggregated states (photoluminescence in solids and aggregation‐induced emission in solutions), as well as reversible redox properties in electrochemical performance.